Memoria y representación de la illa andina en los documentos de la colonia - Mautino Guillén, Alejandro Giancarlo (2021)
This research addresses the cosmic representation of the Andean island and its discourses in various documents of the colony. The theoretical framework that we use is interdisciplinary, as we use literary theory (linked to the category of representation) and anthropology (linked to the nature of the concept of illa in the pre-Hispanic world). Our methodology will employ an integrative textual analysis that emphasizes the role of the linguistic, cultural and social element of the text. Thus, we develop three fundamental sections in our article: first, we inquire about the concept of representation to later focus on colonial texts; secondly, we will stop at the tension dynamics of the Andean illa from these documents and, finally, we will observe the notion of communicative memory and cultural memory in the documents of the colony where the Andean illa is represented.